Study Habits and Their Effects with the Academic Performance of Bachelor of Science in Radiologic Technology Students - B. Oliva, Ameena (International Journal of Scientific Research and Management (IJSRM), 2021)
This study aimed at investigating the effects of students' study habits on their academic performance in professional and general education subjects. To attain this aim, the researcher used a sample of thirty-two (32) students from the Bachelor of Science in Radiologic Technology program under the College of Allied Medical Sciences for the academic year 2019–2020 of a university in Bulacan. The researcher used the descriptive-correlational method of research, which utilized a standardized questionnaire as the primary data gathering technique. Results of the regression analysis indicate that all eight (8) variables of study habits are correlated with academic performance (professional subjects and general education subjects) of the students to a varying extent, as shown by the non-zero B coefficients. The results of the analysis of variance of the regression of study habits on the academic performance of the students revealed an F ratio of 0.939 and 0.900 with an associate probability equal to 0.505 and 0.533, respectively. Since the p-values are greater than alpha, the null hypothesis (Ho) cannot be rejected. It may be safely concluded that the study habits of the students did not produce significant combined effects on the academic performance of the students. Conclusions were drawn, and recommendations were offered.